HUBUNGAN PENGETAHUAN KESEHATAN OLAHRAGA TERHADAP PENCEGAHAN PENGGUNAAN DOPING PADA ATLET ATLETIK - Nimrot Manalu; Dimmichael Ginting; Febrina Panggabean; Remika Situmorang; Sundari Ramahsita (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to determine the relationship between sports health knowledge and the prevention of doping use among athletics athletes. The problem addressed in this study is based on the ongoing risk of doping use among athletes due to the lack of understanding regarding sports health and the dangers of prohibited substances. This research employed a quantitative approach with a correlational design. The sample consisted of 30 athletics athletes who were actively training and had participated in competitions, selected through purposive sampling techniques. Data were collected using a Likert-scale questionnaire that had been tested for validity and reliability. The data were analyzed using descriptive analysis and Pearson Product Moment correlation analysis with the assistance of SPSS software. The results showed that the athletes’ level of sports health knowledge was in the good category, while the level of doping prevention was in the high category. The correlation test results indicated a correlation coefficient value of 0.672 with a significance value of 0.000 < 0.05. These findings indicate that there is a positive and significant relationship between sports health knowledge and the prevention of doping use among athletics athletes. The higher the athletes’ sports health knowledge, the higher their awareness and efforts to prevent doping use. Therefore, sports health education and anti-doping socialization programs need to be improved to create a healthy, safe, and fair play-oriented sports environment.